ESTIMATION OF SEX FROM ORBITAL INDEX – AN ANTHROPOLOGICAL METRIC BASED STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Human orbit is one such area where many investigators have a vested interest for its use in identification due to its dimorphic features. Aims and Objectives: 1. To determine sex with the help of orbital index. 2. To analyze and compare the measurements of right and left orbital index in dry skulls and to see their statistical significance. 3. To derive the regression formula of orbital index for sex identification. Materials and Methods: A cross-sectional study was conducted using seventy-two dry skulls (47 males and 25 females) obtained from the departmental museums of Forensic Medicine and Anatomy. The morphometric values were recorded, orbital index was calculated, and all parameters were analysed, followed by independent ‘t’ test and discriminant function analysis.
Keywords: Forensic Anthropology; Dacryon; Orbital Index; Skull; Sexual Dimorphism; Sex estimation